The Application of Islamic Spiritual Methods in Nursing Program Curriculum at UIN Syarif Hidayatullah Jakarta and UIN Alauddin Makasar - Dwi Setiowati; Peggy Rianti Kurnia Sukma; Rasdiyanah Rahim (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
This research focuses on describing the implementation of Islamic spiritual care of the clinical nursing students at the State Islamic University (UIN). The implementation of Islamic spiritual care has not been done well by nurses. Clinical nursing students are the forerunners of nurses, but no one has examined the description of the application of Islamic spiritual care carried out by clinical nursing students in State Islamic University (UIN). This research method was descriptive quantitative. Samples were students of the clinical nursing students of UIN Jakarta and UIN Alauddin Makassar, 40 respondents. The results showed that most respondents applied Islamic spiritual care well (52.5%). The most well-implemented component is instilling optimism for healing that comes from God (60%). Students need to improve their self-competence in Islamic religious knowledge to become more competent in providing Islamic care to patients. The head of the clinical nursing program needs to emphasize efforts to increase Islamic spiritual competence in the clinical practice setting of learning guidelines through the guidance process and learning achievement targets.Penelitian ini berfokus untuk mengetahui penerapan perawatan spiritual Islam mahasiswa Ners di Universitas Islam Negeri (UIN). Penerapan asuhan keperawatan secara holistik khususnya dalam aspek spiritual karena masih sangat minim dilakukan oleh perawat di tatanan pelayanan keperawatan. Mahasiswa merupakan cikal bakal perawat dan peneliti belum menemukan penelitian tentang penerapan perawatan Islam oleh mahasiswa Ners di lingkungan UIN. Metode yang digunakan yaitu deskriptif kuantitatif. Sampel yang digunakan yaitu mahasiswa Ners UIN Jakarta dan UIN Makassar masing-masing 40 responden. Hasil menunjukkan sebagian responden menerapkan perawatan spiritual Islam dengan baik (52,5%). Komponen yang paling banyak diterapkan dengan baik yaitu menanamkan optimisme kesembuhan yang datang dari Allah (60%). Mahasiswa perlu meningkatkan kompetensi diri dalam ilmu agama islam sehingga menjadi lebih kompeten dalam mebrikan perawatah islam kepada paeien, program studi Ners perlu lebih menekankan pada upaya peningkatan kompetensi spiritual islam pada tatanan praktik klini pedoman pembelajaran, melalui proses bimbingan maupu target capaian pembelajaran.